Why manage our forests? - Colorado State Forest Service, author (Colorado State University. Libraries, 2016)
As a visitor to the Colorado State Forest, you've likely come here to enjoy its aesthetics, solitude and wild, undeveloped setting. You might wonder what's happening to the forestland when you see broad swaths of beetle-killed trees or clearings created by recent timber-harvesting operations. While changes like these may seem dramatic, these forests are dynamic, undergoing constant change, and forest management plays a critical role in the long-term health of the State Forest.
Established in 1938, the Colorado State Forest is a 71,000-acre property in north-central Colorado managed by the State Land Board (SLB). Here forestry, grazing, recreation and wildlife coexist on a working landscape that generates revenue for Colorado public schools. The CSFS manages the forest resources through an agreement with the SLB.
Keywords: Colorado; ecology; lodgepole pine; mountain pine beetle; forest management